PWE-114 Gastrostomy insertion: beyond the mortality rates. (8th June 2018) - Hulley, Joanne Louise; Ramful, Satyasheel; Thompson, Nick
Abstract : Introduction: Short-term mortality rates from percutaneous endoscopic gastrostomy (PEG) insertion are well documented and often the focus of audit. Our Northern Nutrition Network extends across nine trusts in the North East and Cumbria, comprising of gastroenterologists, dietitians and specialist nurses. We analysed our regional population. Methods: 3 months of prospective data were collected on patients undergoing PEG or radiologically inserted gastrostomy (RIG); focussing on mortality, premorbid state, complications and sedation use. 90 day outcomes were recorded. Results: 146 gastrostomies were inserted, with a 30 day mortality rate of 8.2% (12/146) and 90 day mortality rate of 17.5% (26/146). Our 30 day mortality included a 2% (3/146) risk of dying in the first 7 days after gastrostomy; deemed attributable to the procedure. Indications for gastrostomy included; ENT/UGI obstruction/malignancy (46/146), neurological conditions (20/146), stroke (31/146), depressed consciousness (17/146), malnutrition (4/146) and failure of function (13/146). 88 patients were female, 56 were male. The average ASA was 2.7; mean BMI was 23.5; mean albumin was 37; mean age was 66 years. The 30 day mortality group had a higher mean age (76.7 vs. 66 years) and ASA (3.1 vs. 2.7), and a lower BMI (18.5 vs. 23.5) and albumin (31 vs. 37), suggesting these factors, which are associated with frailty, could impact on mortality. We found a complication rate of 27% (40/146) and a statistically significant link between mortality and complications. The 30 day mortality increased from 4.7% (5/106) to 17.5% (7/40) if a complication occurred (p=0.012). This was reflected in the 90 day mortality group, where mortality increased from 13% (14/106) in the group with no complications to 30% (12/40) in the complication group (p=0.018). The most common complication was pneumonia, at 11% (16/147). The risk of pneumonia could be linked with sedation use, as the group receiving midazolam sedation (average 2 mg per patient) had a pneumonia rate of 13.7% (15/109) whereas in the un-sedated group only one patient suffered pneumonic complications (n=11). There were no reported cases of pneumonia in the 26 patients who underwent general anaesthetic for the procedure. Conclusion: We report similar mortality rates to previous studies. Our data follow the trend that older, sicker, less well-nourished patients have poorer outcomes following gastrostomy insertion than their younger, fitter, counterparts. We have shown a statistically significant link between increasing mortality and complications. Likewise, our data suggest that sedation is a risk factor for our most common complication; pneumonia. Careful patient selection and realistic conversations with patients and relatives prior to gastrostomy insertion remain paramount.